Carbon monoxide improves haemodynamics during extracorporeal resuscitation in pigs. Issue 1 (14th March 2019) - Wollborn, Jakob; Steiger, Christoph; Ruetten, Eva; Benk, Christoph; Kari, Fabian A; Wunder, Christian; Meinel, Lorenz; Buerkle, Hartmut; Schick, Martin A; Goebel, Ulrich
Abstract: Aims: Heart disease of different aetiology remains the leading cause of cardiac arrest (CA). Despite efforts to improve the quality of cardiopulmonary resuscitation (CPR), subsequent myocardial and systemic damage after CA still present a major long-term burden. Low-dose carbon monoxide (CO) is known to exert protective effects in cardiovascular pathophysiology but clinical applications are challenged by unfavourable delivery modes. We tested the hypothesis that extracorporeal resuscitation (E-CPR) in combination with controlled fast onset CO delivery results in improved cardiac physiology and haemodynamics. Damage-associated molecular pattern (DAMP) signalling may be part of the molecular mechanism. Methods and results: In an established porcine model, E-CPR was performed. While E-CPR leads to similar results as compared to a conventional CPR strategy, CO delivery in combination with E-CPR demonstrated significant cardioprotection. Cardiac performance analysis using echocardiography and thermodilution techniques showed a CO-dependent improved cardiac function compared to severe myocardial dysfunction in CPR and E-CPR (left ventricular ejection fraction: Sham 49 ± 5; CPR 26 ± 2; E-CPR 25 ± 2; CO-E-CPR 31 ± 4; P < 0.05). While sublingual microcirculation was significantly compromised in CPR and E-CPR, CO delivery demonstrated a significant improvement in microvascular function (microvascular flow index: Sham 2.9 ± 0.1; CPR 2.2 ± 0.1; E-CPR 1.8 ± 0.1; CO-E-CPR 2.7 ± 0.1; P < 0.01). Histological and serological myocardial damage markers were significantly reduced (hsTroponin-T Sham 0.01 ± 0.001; CPR 1.9 ± 0.2; E-CPR 3.5 ± 1.2; CO-E-CPR 0.5 ± 0.2 ng/mL; P < 0.05). DAMP signalling was decreased ipse facto leading to influence of cardioprotective heat shock and cyclooxygenase response. Conclusions: CO treatment restores myocardial function and improves systemic macro- and microhaemodynamics in E-CPR through a reduction in DAMPs.